AB0299 COXITIS DURING CHRONIC INFLAMMATORY RHEUMATISM. (June 2019) - abla, hedia ben; Rekik, Sonia; Jammali, Samia; Boussaid, Soumaya; Sahli, Hela; Cheour, Elhem; Elleuch, Mohamed
Abstract : Background: The occurrence of coxitis in chronic inflammatory rheumatism is a prognostic factor of great importance given the functional repercussions of the involvement of the coxofemoral joint. Objectives: The aim of this work is to evaluate the prevalence of this lesion in chronic inflammatory rheumatism (PR/JIA/SpA) and to describe the evolution of this disorder according to the pathology. Methods: Eighty-two patients with chronic inflammatory rheumatism were enrolled. These patients were followed by the rheumatology department rabta since 2004 until March 2018. The clinical demographics, activity scores, treatment background (all our patients in this series were under biotherapy) and the need PTH were identified. Results: The eighty-two patients were distributed as follows: 36.58% (n = 30) patients with RA, 36.58% (n = 30) SpA and 26.83 (n = 22) JIA. The average age was 48.3 years, 47.6 years and 32.17 years. For the rheumatoid arthritis population 26.67% (n = 8) of the patients had a coxite of which 62.5% (n = 5) was bilateral and 37.5% (n = 3) unilateral. The mean time to discovery of coxite was 11.7 years and the evolution was in 50% (n = 4) to worsening requiring in 3 cases a bilateral PTH and a case of synoviorthesis. In the SpA group, 23.33% (n = 7) of patients had coxitis, of which 57.14% (n = 4) were bilateral and 32.86% (n = 3) unilateral. The average time to discovery was 8.22 years. PTH was performed in 71.43% (n = 5) of patients. For the JIA population, 45.45% (n = 10) of the patients had a coxite of which 80% (n = 8) was bilateral and 20% unilateral. The average time to discovery of this lesion was 14 years, with 60% of cases progressing to an aggravation requiring 40% of the cases for synoviorthesis and 60% for PTH. Conclusion: SpA is the most common chronic inflammatory rheumatism with cxo-femoral involvement with the most pejorative evolution despite the biological treatment References: none Disclosure of Interests: None declared